Renesans urodzin. Obyczajowy "niuans" w kontekstach kulturowych, historycznych, religijnych i literackich = Renaissance of birthdays. The customs' "nuance" in cultural, historical, religious and literary contexts - Kulczycka, Dorota (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Birthday is the custom having its roots in ancient Mesopotamia, Egypt, Greece and Rome, as well as being widespread in Protestant countries. This tradition has been very popular in Poland for years. The author notices that celebrating birthdays used to be reserved for children only, whereas nowadays it is becoming more and more popular among adults.
Keywords: urodziny; imieniny; transformacje w dziedzinie obyczajowości; badania kulturowe; literatura dla dzieci i młodzieży; film; birthday; name day; customs' transformations; cultural research; literature for youth and children